Spin : Psychological Scientists Use Casual Language to Describe Non-Casual Data - Bleske-Rechek, April L.; Gunseor, Michaela M. (My University, 2018)
Misrepresentation of data, or “spin,” comes in various forms and can be intentional or unintentional. One of the most prevalent forms of spin involves misleading interpretation – specifically, making causal claims that are not supported by the findings or research design.5 Researchers in the allied health disciplines, education, and counseling have voiced concern about unjustified causal claims and have encouraged researchers to match the language they use in their reports to the specific type of study they have conducted. Here, we investigate the frequency with which scientists in psychology use unwarranted causal language in scholarly descriptions of their work.
Color poster with text, table, and images.
Keywords: Posters; Psychology; Causal language; Data misrepresentation; Spin; Causal claims